Isolation and identification of a new Colletotrichum species causing anthracnose of Astragalus membranaceus. (May 2021) - Jin, Mengjun; Yang, Chengde; Yang, Liping; Cui, Lingxiao; Wei, Lijuan
Abstract: Anthracnose is regarded as a destructive disease in agriculture. In this study, the disease symptoms of black dots on Astragalus membranaceus, similar to those of anthracnose reported previously, were investigated at Weiyuan, Gansu province, China, in September 2019. A strain named GW4-7 was initially isolated and identified as the Colletotrichum species with curved conidia. Moreover, the pathogenicity tests confirmed that the strain induced obvious anthracnose symptoms on A. membranaceus, which were consistent with those originally observed in the field. Subsequently, the multilocus phylogenetic analysis of the partial sequences of internal transcribed spacer ( ITS ), actin ( ACT ), and glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ) genes of this strain indicated that the A. membranaceus strain GW4-7 was most closely clustered with Colletotrichum spinaciae . To our knowledge, this is the first report of C. spinaciae as a causal agent of anthracnose on A . membranaceus in China. Highlights: A new record of Colletotrichum spinaciae in China. Anthracnose symptom was observed on the stems of Astragalus membranaceus. The strain was identified with morphological and molecular characteristics. C. spinaciae as a causal agent causing anthracnose on A. membranaceus.